A comparison of intraoperative 3D and conventional 2D fluoroscopy to detect screw misplacement in volar plate osteosynthesis of the distal radius - Brunken, Fenna; Bullert, Benno; Morlock, Livia; Gierse, Jula; Grützner, Paul Alfred; Vetter, Sven Y.; Beisemann, Nils (Journal of Clinical Medicine, 2025)
Background/Objectives: Dorsal screw protrusion or intra-articular screw penetration at the distal radius can cause extensor tendon injuries or articular surface damage. Despite the use of various views, the detection of screw misplacement remains limited in 2D fluoroscopy. This study compares the sensitivity of 2D and 3D fluoroscopy for detecting screw misplacement at the distal radius. Methods: Volar locking plates were placed in six cadaveric forearms, and dorsal or intra-articular screw misplacement was induced. For each screw position, images were acquired by 2D and 3D fluoroscopy and assessed by three blinded observers. Sensitivity and specificity, inter-rater agreement, and observer confidence were evaluated. The dose area product (DAP) was measured separately for 2D and 3D fluoroscopy. Results: Three-dimensional fluoroscopy showed higher sensitivities for detecting dorsal (97.22%) and intra-articular (95.83%) screw misplacements than two-dimensional fluoroscopy. In 2D fluoroscopy, sensitivity for detecting dorsal screw protrusions improved from 63.89 to 75.00–77.78% with the inclusion of tangential views. For intra-articular penetrations, sensitivity in 2D fluoroscopy increased from 79.17 to 83.33% with the addition of oblique views. Observer confidence was higher in 3D fluoroscopy. DAP was significantly higher in 3D (42.4 ± 0.4 cGycm2) compared to 2D fluoroscopy (14.2 ± 3.7 cGycm2) (p < 0.0001). Conclusions: Compared to 2D fluoroscopy, 3D fluoroscopy improves the detection of screw misplacement at the distal radius. However, its routine use is constrained by increased radiation exposure and limited availability. If 3D fluoroscopy is not accessible, the addition of dorsal tangential and oblique views may improve the sensitivity of 2D fluoroscopy.
Gesehen am 08.01.2026